2010
DOI: 10.1021/nn102697r
|View full text |Cite
|
Sign up to set email alerts
|

Orienting Periodic Organic−Inorganic Nanoscale Domains Through One-Step Electrodeposition

Abstract: One of the challenges in the synthesis of hybrid materials with nanoscale structure is to precisely control morphology across length scales. Using a one-step electrodeposition process on indium tin oxide (ITO) substrates followed by annealing, we report here the preparation of materials with preferentially oriented lamellar domains of electron donor surfactants and the semiconductor ZnO. We found that either increasing the concentration of surfactant or the water to dimethyl sulfoxide ratio of solutions used r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…The layer formed over the flexible NF substrate indicates the deposition of peptide/Ni(OH) 2 ‐based nanohybrid material. The electrochemical conversion of the dipeptide and Ni(NO 3 ) 2 to peptide/Ni(OH) 2 can be expressed as follows NO3+normalH2O +2normaleNO2+2OHNi2++2OHNi(OH)2…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The layer formed over the flexible NF substrate indicates the deposition of peptide/Ni(OH) 2 ‐based nanohybrid material. The electrochemical conversion of the dipeptide and Ni(NO 3 ) 2 to peptide/Ni(OH) 2 can be expressed as follows NO3+normalH2O +2normaleNO2+2OHNi2++2OHNi(OH)2…”
Section: Resultsmentioning
confidence: 99%
“…The NF was used as the working electrode, Pt wire as the counter electrode and Ag/AgCl as the reference electrode. The organic–inorganic hybrid material was grown on a flexible NF substrate through electrodeposition for 10–60 min by applying −0.9 V constant current and the temperature of the solution was maintained at 60 °C by water bath with continuous magnetic stirring . After the electrodeposition, the deposited thin film surface was washed with ultrapure water and ethanol and dried at 60 °C for 6 h.…”
Section: Methodsmentioning
confidence: 99%
“…Also hydrophilic and more hydrophobic were utilized as well, indium tin oxide (ITO) surfaces and or more hydrophobic poly(2,3‐dihydrothieno‐1,4‐dioxin)‐poly(styrene sulfonate) (PEDOT:PSS), respectively. [ 127b ] Through this work, it was found that less hydrophobic chromophore amphiphiles result in similar isotropic orientation on both surfaces ( Figure a), whereas the hydrophobic linker results in parallel orientation on the hydrophilic ITO surface and perpendicular orientation on PEDOT:PSS (Figure 22b). To reveal the mechanism of this orientation, decanoic acid was used as a surfactant in place of the chromophore amphiphile.…”
Section: Organic–inorganic Hybrid Materials With Supramolecular Strucmentioning
confidence: 86%
“…Molecular design and substrate chemistry can be used to control the orientation of the resultant hybrid in electrodeposited chromophore amphiphile–inorganic hybrids, offering a new handle to control properties. [ 127 ] It was first observed that modulating the chemistry of the substrate can be leveraged to control the orientation of the lamellar flakes of pyrenebutyric acid zinc hydroxide hybrids where hydrophilic polystyrene sulfonate surfaces resulted in primarily parallel orientation of the hybrid layers to the surface. [ 127a ] This was investigated further with molecules containing no linker between the chromophore and binding group or a hydrophobic alkane linker.…”
Section: Organic–inorganic Hybrid Materials With Supramolecular Strucmentioning
confidence: 99%
See 1 more Smart Citation